Implementasi Pendidikan Pancasila dalam Kurikulum Merdeka: Studi Kasus SMK Negeri 8 Kota Tangerang Selatan - Putri, Riska; Suwandi; Putri, Mas Fierna Janvierna Lusie; Sulastri; Nurdiyana (CV. Kurnia Grup, 2024)
This study explores the implementation of Pancasila Education in the Merdeka Curriculum at SMK Negeri 8 Kota Tangerang Selatan. Using a qualitative approach and in-depth interviews, the research reveals that project-based learning methods enhance students` independence and active participation in the learning processs. Projects such as creating videos on nationalism enable students to apply Pancasila values in real-world contexts. However, limited resource support from the education authorities poses significant challenges. Pancasila Education teacher, Ms. Nadya Kartika Putri, emphasized the importance of project-based evaluation to comprehensively assess students` understanding. This study highlights the need for collaboration between schools and policymakers to improve learning effectiveness. In conclusion, the Merdeka Curriculum positively impacts students` understanding of Pancasila values, through better support is necessary for optimal implementation.